Determinants of the Spread in a Two-Tier Foreign Exchange Market. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
The literature on two-tier foreign exchange markets has concentrated on relating various shocks to the spread between the exchange rates relevant to the two tiers of the exchange market. In some earlier work we found that none of the typical predictions of theory held up empirically as BLEU spread explanations. In particular we could not find any domestic policy variables that significantly explained the BLEU spread. Our finding led us to reformulate two-tier market theory. We find that if domestic agents are risk neutral then no domestic policy variables are predicted to influence the spread.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Bond Purchase; Cross-Market Leakage; Domestic Policy; Exchange-Rate Uncertainty; WP; Belgium